Condorcet : Writings on the United States - Condorcet, Jean-Antoine-Nicolas de Caritat, marquis de, 1743-1794 (Book collections on Project MUSE., 2012)
"An English translation of the writings of French constitutional theorist Nicolas de Condorcet (1743-94) on the United States. Subjects include the American Revolution, federal Constitution, and the emerging political culture in the United States"--Provided by publisher.